Assisting Elementary School Personnel to Better Serve and Support Immigrant and Latine Heritage Children. Issue 1 (22nd January 2021) - Garcia, Martha Lucia
Abstract: A 2019 United Nations (UN) report declared the need for educational support by teachers for immigrant and refugee children across the world. These children directly or indirectly experience trauma throughout the migration process, which manifests in different aspects of their development. At the educational level, trauma can affect children's ability to concentrate and learn. Trainings on trauma-informed teaching may not include the specific forms of trauma experienced by immigrant children during stages of migration or the impact of trauma caused by war, or the hatred that leads to genocide. This makes invisible the extreme, repeated, or varied traumatic events that may have been lived by children escaping from Central America's Northern Triangle, which includes El Salvador, Guatemala, and Honduras. Teachers working with immigrant children need this information to be able to adapt their lessons and teaching style to meet children's needs. The study discussed in this article attempts to address the reactions of trauma and fear on immigrant children by training and supporting teachers and staff in an elementary school who work with "Latine" children. This article presents a tested training module that responds to the call by the UN to assist immigrant children through the training of school personnel.